Specific suppressor T cells for delayed-type hypersensitivity in susceptible mice immunized against cutaneous leishmaniasis. - Dhaliwal, J S (1985)
BALB/c mice injected intravenously with 10(6) or higher doses of formaldehyde-fixed promastigotes (ffp) of Leishmania major developed significantly lower levels of delayed-type hypersensitivity (DTH) compared with uninjected control mice when they were subsequently immunized intradermally with ffp. The suppression of DTH was antigen specific and was also inducible with lethally irradiated promastigotes or soluble parasite antigens. The suppressive effect was adoptively transferable with splenic T cells which express the Lyt-1+2+ and L3T4+ phenotypes. These specific suppressor T cells were active against both the inductive and expressive phases of DTH. They were sensitive to 200 rads of gamma-irradiation in vitro and appeared to manifest the suppressive activity via soluble factors. In spite of this profound suppression of DTH, BALB/c mice injected intravenously with 4 X 10(7) ffp were substantially protected against a challenge infection with L. major promastigotes. The possible relationship between the suppressor T cells for DTH and prophylactic immunization against fatal cutaneous leishmanial infection in susceptible BALB/c mice is discussed.